Training Needs Analysis: Enhancing Organizational Development Competence for Elementary School Principals - Febrizon, Egi; Rusdinal, Rusdinal; Hadiyanto, Hadiyanto (International Conference on Elementary Education, 2020)
This research is motivated by the low competency of principals in organizational development. The various training programs that have been held have not had a significant impact on increasing the competency of principals. The failure of the training program was due to the training being top down and not based on the real needs of the principal. An analysis of training needs must be carried out prior to the training to determine the competencies that need to be improved through training. Theobjectives of this research is to analyze the need of principals training in organizational development competence. This research was conducted using descriptive method. Data analysis was done descriptively. The results showed the average needs of primary school principals on the readiness of school principals in implementing change was 74 (in the need category), an indicator of organizational structure was 67 (in the quite need category), The job division indicator is 69 (in the need category), and the understanding and application of information and communication technology (ICT) is 86 (in the very need category). So, it can be concluded that the most important need is the understanding and application of ICT in schools with 86